2016
DOI: 10.3390/s16111798
|View full text |Cite
|
Sign up to set email alerts
|

Information Fusion of Conflicting Input Data

Abstract: Sensors, and also actuators or external sources such as databases, serve as data sources in order to realise condition monitoring of industrial applications or the acquisition of characteristic parameters like production speed or reject rate. Modern facilities create such a large amount of complex data that a machine operator is unable to comprehend and process the information contained in the data. Thus, information fusion mechanisms gain increasing importance. Besides the management of large amounts of data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 80 publications
(98 reference statements)
0
22
0
4
Order By: Relevance
“…Mönks et al focused on the fuzzified balanced two-layer conflict solving (µBalYLCS) algorithm, which originates from DS theory and operates on fuzzy sets. The algorithm works well in situations with high data conflict [18]. Furthermore, Lu et al [19] have confirmed the effectiveness and usefulness of fuzzy logic combined with an extension of DS theory in data fusion.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Mönks et al focused on the fuzzified balanced two-layer conflict solving (µBalYLCS) algorithm, which originates from DS theory and operates on fuzzy sets. The algorithm works well in situations with high data conflict [18]. Furthermore, Lu et al [19] have confirmed the effectiveness and usefulness of fuzzy logic combined with an extension of DS theory in data fusion.…”
Section: Introductionmentioning
confidence: 86%
“…, 100) be an array of 100 discrete Andrews' curve values and i be indices from 2 to 99 (since G(1) and G(100) cannot be the candidates). G[i] can be defined as a PP if it satisfies Equation (17); otherwise, it can be defined as an NP by Equation (18).…”
Section: Type Of Andrews' Curve Dynamic (Tad)mentioning
confidence: 99%
See 1 more Smart Citation
“…Its basic concept is summarised in the following. The entire theoretical background is elaborated in [6,11]. MACRO’s structure is depicted in Figure 1.…”
Section: Related Workmentioning
confidence: 99%
“…For more information on the human group decision-making background of MACRO, the reader is referred to [6,12]. It was shown that the application of this approach for condition monitoring purposes is beneficial compared to state-of-the-art approaches [6,11,13]. …”
Section: Related Workmentioning
confidence: 99%